INTRODUCTION TO DIGITAL LITERACY FOR PARENTS THROUGH THE "E.LIST" APPLICATION FOR STUNTING EDUCATION IN BOTUMOITO DISTRICT GORONTALO PROVINCE - Jusuf, Herlina; Adityaningrum, Amanda; Arsad, Nikmatisni; Rahim, Eman (Jurnal Pengabdian Kesehatan Masyarakat, 2023)
The Indonesian Ministry of Health reports that until 2022, the prevalence of stunting in Gorontalo Province will still be higher than the standards set by WHO. Providing education to parents about stunting can contribute to stunting prevention. The novelty of this service article is that it introduces digital literacy to parents through the "E.LIST" application for stunting education. This community service activity aims to empower parents with an application-based digital literacy program called "E.LIST" for stunting education. According to the Indonesian Ministry of Communication and Information, the 2022 National Digital Literacy Index increased by 0.05 points compared to the 2021 index results. Therefore, smartphones and their applications can be used to facilitate the provision of health services and health education, including stunting prevention. The Waterfall System Development Life Cycle (SDLC) method is used to create applications, which consists of gathering information, designing software, implementing, testing, and operating and maintaining. For Gorontalo Province, Boalemo Regency has the second highest stunting prevalence, 29.9%, which is still above the WHO recommended figure. Furthermore, based on preliminary information from the Boalemo District Health Service, it is estimated that 62 children in Botumoito District are stunted. The results of activities through this application are that parents in Botumoito District can improve education about stunting and health services related to stunting. Conclusion: The "E.LIST" application provides a simple method for receiving healthcare and health education, monitoring the development of babies under five, and completing independent assessments. The applications were designed to meet the needs and characteristics of parents.